FALKLANDS/MALVINAS 1982 ([S.l.])
1 online resource
Keywords: After four decades from the 1982 war between Britain and Argentina over possession of the Falklands/Malvinas islands in the South Atlantic Ocean, this book allows for a new and rounded reading of the causes, course and consequences of the war. It provides a comprehensive overview of the Falkland/Malvinas War by integrating the military history of the conflict into the diplomatic, political, social and cultural aspects of the war. Including a substantial body of advocacy, chronicle, narrative and analysis, the volume draws upon an extensive range of published sources, in English and Spanish, primary sources from both sides and unpublished testimonies. The book, written by Argentine and Australian historians and scholars, discuss themes such as the background to the war, the offensive campaign for the islands and the English and Argentine experiences and memories of the war from the perspective of the islanders. Being part of the Wars and Battles of the World series, this book will be an essential read for scholars and researchers of military history, British history, Latin American history, defence and strategic studies, geopolitics and modern history.